2023
DOI: 10.1007/s00167-023-07532-7
|View full text |Cite
|
Sign up to set email alerts
|

Joint line obliquity after lateral closing‐wedge high tibial osteotomy does not adversely affect clinical and radiological outcome: a 5‐year follow‐up study

Abstract: Purpose To analyze the association between change in knee joint line obliquity (KJLO) and patient-reported outcome, radiological progression of osteoarthritis, and surgical survival after lateral closing-wedge high tibial osteotomy (HTO). Methods A cohort of 180 patients treated in one single hospital with lateral closing-wedge HTO was examined. KJLO was defined by the medial proximal tibial angle (MPTA). To assess the association between KJLO and patient-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 68 publications
0
1
0
Order By: Relevance
“…In addition, complex biomechanics may have contributed to the statistical significance. Many recent studies on JLO associated with HTO have been reported [38][39][40][41]; however, most covered the association between postoperative JLO and clinical outcomes. The association between preJLO and ΔJLCA seems to be an area that requires further study.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, complex biomechanics may have contributed to the statistical significance. Many recent studies on JLO associated with HTO have been reported [38][39][40][41]; however, most covered the association between postoperative JLO and clinical outcomes. The association between preJLO and ΔJLCA seems to be an area that requires further study.…”
Section: Discussionmentioning
confidence: 99%